Perancangan Network Monitoring Tools Menggunakan Autonomous Agent Java - S, Khurniawan Eko; A, Lalu Ahmad S. Irfan; Widiartha, I B K (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi, 2016)
Network management tasks are performed by the Network Administrator such as gathering available network resources information. The SNMP (Simple Network Management Protocol) Technology provides flexibility for network administrators in managing the overall network from a single location. Agent based Network Monitoring Tools JAVA Application consists of Master agent whose job is to perform as well as the management agent Request and  database access. The Request agent in charge for monitoring servers that implement SNMP4j library with multi - agent systems. For interface, Network Monitoring Tools application using web media as an administrator interface that can be used from anywhere and at anytime. The results of this study showed that the application as a Network Monitoring Tools are able to work with the percent error in the range of 0-18 % . Besides these applications generate trend data readout server more stable and faster than the application Cacti do. This is supported by the ability of the Request Agent to respond the level of server workloads .
Keywords: Agent; JAVA; SNMP; Cacti; Network monitoring.